Direct laser written polymer waveguides with out of plane couplers for optical chips - Landowski, Alexander; Zepp, Dominik; Wingerter, Sebastian; Von Freymann, Georg; Widera, Artur (APL Photonics, 2017)
Optical technologies call for waveguide networks featuring high integration densities, low losses, and simple operation. Here, we present polymer waveguides fabricated from a negative tone photoresist via two-photon-lithography in direct laser writing, and show a detailed parameter study of their performance. Specifically, we produce waveguides featuring bend radii down to 40 μm, insertion losses of the order of 10 dB, and loss coefficients smaller than 0.81 dB mm-1, facilitating high integration densities in writing fields of 300 μm×300 μm. A novel three-dimensional coupler design allows for coupling control as well as direct observation of outputs in a single field of view through a microscope objective. Finally, we present beam-splitting devices to construct larger optical networks, and we show that the waveguide material is compatible with the integration of quantum emitters.
CRIS-Team Scopus Importer:2023-03-27